Management Impacts on Soil Organic Matter of Tropical Soils - Castro, Gustavo S. A.; Crusciol, Carlos A. C. [UNESP]; Calonego, Juliano C.; Rosolem, Ciro A. [UNESP] (Soil Sci Soc Amer, 2015)
Increased soil organic matter (SOM) improves the cation exchange capacity of tropical weathered soils, and liming is required to achieve high yields in these soils. Despite a decrease in SOM in the short term, liming may increase SOM with time by improving cation chemical bonds with soil colloids. Soil C may also be increased in high dry matter input cropping systems. We evaluated C changes in a Typic Rhodudalf as affected by four production systems with increasing residue inputs, with or without limestone or silicate. Soil use intensification by increasing the number of species in rotation as well as acidity remediation resulted in higher plant residue production. Introducing a green manure or a second crop in the system increased plant residue by 89% over fallow, but when a forage crop was used, plant residues more than doubled. Soil acidity amelioration increased plant residue deposition by 21% over the control. The introduction of a forage crop increased labile SOM and C contents in the particulate fraction, and lime or silicate application led to increases in the more stable SOM fraction. High amounts of plant residues (>70 Mg ha(-1) in 5 yr) are effective in raising soil labile C, but the alleviation of soil acidity results in increased soil stable C irrespective of crop rotations in tropical weathered soils, and in this case plant residue deposition can be lower. Lime and silicate are equally effective in alleviating soil acidity and increasing soil C, probably due to the formation of cation bridges with soil colloids.